Moralizing Postcolonial Consumer Society: Fair Trade in the Netherlands, 1964–1997*. (29th July 2016) - van Dam, Peter
Abstract: Decolonization challenged people across the globe to define their place in a new postcolonial order. This challenge was felt in international political and economic affairs, but it also affected daily lives across the globe. The history of fair trade activism as seen from the Netherlands highlights how citizens in the North grappled to position themselves in a postcolonial consumer society. Interventions by fair trade activists connected debates about the morals of their society to the consequences of decolonization. They reacted to the imbalances of the global market in the wake of decolonization, joining critics from the South in demanding more equitable global relations. It was around this issue of "fair trade" that a transnational coalition of moderate and more radical activists emerged after the 1960s. This coalition held widely dissimilar views regarding the politics of the left and the use of consumer activism. The analysis of their interventions demonstrates that during the postwar era attempts at transforming the global market were inextricably interwoven with visions of a postcolonial order. TRANSLATED ABSTRACTSFRENCH – GERMAN – SPANISH: Peter van Dam. En moralisant la société de consommation postcoloniale. Le commerce équitable aux Pays-Bas, 1964–1997 . La décolonisation a mis au défi des gens dans le monde entier de définir leur place dans un régime postcolonial. Ce défi a été ressenti dans les affaires internationales politiques et économiques, mais il a également affecté des vies quotidiennes dans tous les pays. L'histoire de l'activisme du commerce équitable, vue à partir des Pays-Bas, illustre comment des citoyens au Nord se sont débattus pour se positionner dans une société de consommation postcoloniale. Les interventions des activistes du commerce équitable ont raccordé les débats sur la moralité de leur société aux conséquences de la décolonisation. Ils ont réagi aux déséquilibres du marché mondial dus à la décolonisation, rejoignant les critiques dans le Sud exigeant des relations mondiales plus équitables. C'est autour de cette question du "commerce équitable" qu'une coalition transnationale d'activistes modérés et plus radicaux est apparue après les années 1960. Cette coalition avait des opinions extrêmement différentes concernant la politique de la gauche et l'utilisation de l'activisme des consommateurs. L'analyse de leurs interventions démontre que pendant l'ère de l'après-guerre, les tentatives pour transformer le marché mondial et des visions d'un ordre postcolonial étaient inextricablement imbriquées les unes dans les autres. Traduction: Christine Plard Abstract : Peter van Dam. Die Moralisierung der postkolonialen Konsumgesellschaf. Fair Trade in den Niederlanden, 1964–1997. Die Dekolonisierung hat Menschen in aller Welt vor die Herausforderung gestellt, in der neuen postkolonialen Ordnung ihren Platz zu finden. Diese Herausforderung machte sich in internationalen politischen und wirtschaftlichen Angelegenheiten bemerkbar, doch sie wirkte sich auch weltweit auf das Alltagsleben aus. Die Geschichte des FairTrade-Aktivismus, wie sie sich aus niederländischer Perspektive darstellt, zeigt, wie die Bürger des globalen Nordens darum rangen, sich in einer postkolonialen Konsumgesellschaft zu positionieren. Die Interventionen von FairTrade-Aktivisten stellten einen Zusammenhang her zwischen Debatten um die Moral der eigenen Gesellschaft und den Folgen der Dekolonisierung. Die Aktivisten reagierten auf die Ungleichgewichte des Weltmarktes im Gefolge der Entkolonialisierung und unterstützten die Forderung von Kritikern aus dem globalen Süden nach gerechteren internationalen Beziehungen. Um die Frage des "fairen Handels" bildete sich nach den 1960er Jahren ein Bündnis moderater und radikalerer Aktivisten. Innerhalb dieses Bündnisses waren sehr unterschiedliche Ansichten zur Politik der Linken und zum Repertoire des Verbraucheraktivismus anzutreffen. Die Analyse der betreffenden Interventionen zeigt, dass Bemühungen um die Transformation des Weltmarktes in der Nachkriegszeit untrennbar verwoben waren mit Visionen einer postkolonialen Ordnung. Übersetzung : Max Henninger Abstract : Peter van Dam. Moralizando la sociedad de consumo postcolonia. El comercio justo en los Países Bajos, 1964–1997 . La descolonización supuso un desafío para todo el mundo en un nuevo orden postcolonial. Este reto se sintió de forma especial en la política internacional y en los asuntos económicos, pero también llegó a incidir en la vida cotidiana de la gente en cualquier lugar del planeta. La historia del activismo por un comercio justo vista desde los Países Bajos pone de relieve como los ciudadanos en el Norte pugnaban por posicionarse en una sociedad de consumo postcolonial. Acciones llevadas a cabo por activistas por el comercio justo pusieron en conexión debates sobre la moral de su sociedad en relación con las consecuencias de la descolonización. Reaccionaron frente a los desequilibrios del mercado global generados por las secuelas de la descolonización, uniéndose a las críticas procedentes del Sur reivindicando unas relaciones globales más equitativas. Fue alrededor de la cuestión del "comercio justo" que emergió una coalición transnacional de activistas, que incluía desde los moderados a los más radicales, después de la década de 1960. Esta coalición mantuvo puntos de vista muy dispares en lo referente a la política de la izquierda y al uso consumo como una herramienta activista. El análisis de sus intervenciones permite demostrar que durante la época de postguerra, los intentos de transformar el mercado global estaban inextricablemente entrelazados con las visiones del orden postcolonial. Traducción: Vicent Sanz Rozalén